A novel lexicographical-based method for trapezoidal neutrosophic linear programming problem - Das, Sapan Kumar; Edalatpanah, S.A; Dash, Jatindra Kumar (Neutrosophic sets and systems, 2021)
The aim of this paper is to introduce a simplified presentation of a new computing procedure for solving trapezoidal neutrosophic linear programming (TrNLP) problem under uncertainties. Therefore, we firstly define the concept of single valued neutrosophic (SVN) numbers and ranking functions. A new strategy is planned for solving the NLP problem without any ranking function. The planned strategy is depends on multi-objective LP (MOLP) issue and lexicographic order (LO). By following the means of planned strategy, the problem is changed into crisp LP (CLP) problem. In addition to this, a theoretical analysis is provided. Numerical examples are illustrated the proposed method and the consequences are in contrast with the distinct choice methods. The outcome shows that the proposed technique defeats the deficiencies and constraints of the existing method. Keywords: Neutrosophic trapezoidal numbers; lexicographic method; linear programming, multi-objective linear programming